2003
DOI: 10.1093/emboj/cdg451
|View full text |Cite
|
Sign up to set email alerts
|

VIVID is a flavoprotein and serves as a fungal blue light photoreceptor for photoadaptation

Abstract: Blue light regulates many physiological and developmental processes in fungi. Most of the blue light responses in the ascomycete Neurospora crassa are dependent on the two blue light regulatory proteins White Collar (WC)-1 and -2. WC-1 has recently been shown to be the ®rst fungal blue light photoreceptor. In the present study, we characterize the Neurospora protein VIVID. VIVID shows a partial sequence similarity with plant blue light photoreceptors. In addition, we found that VIVID non-covalently binds ā avi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
320
1
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(334 citation statements)
references
References 45 publications
11
320
1
2
Order By: Relevance
“…A second blue light photoreceptor (ENVOY), the orthologue of the N. crassa VIVID (Heintzen et al, 2001;Schwerdtfeger & Linden, 2003), was first identified in T. reesei (Schmoll et al, 2004). ENVOY, a small protein that contains a single PAS/LOV domain, is also encoded in the genomes of T. atroviride and T. virens.…”
Section: Envoy a Tiny But Nonetheless Important Blue Light Photorecementioning
confidence: 99%
“…A second blue light photoreceptor (ENVOY), the orthologue of the N. crassa VIVID (Heintzen et al, 2001;Schwerdtfeger & Linden, 2003), was first identified in T. reesei (Schmoll et al, 2004). ENVOY, a small protein that contains a single PAS/LOV domain, is also encoded in the genomes of T. atroviride and T. virens.…”
Section: Envoy a Tiny But Nonetheless Important Blue Light Photorecementioning
confidence: 99%
“…Following a dose of light, WC-1 becomes hyperphosphorylated, and this transient phosphorylation is essential for induction of rapid blue-light-inducible genes (Schwerdtfeger & Linden, 2003). In dark-grown cells and light-adapted cells, protein kinase C (PKC) is thought to phosphorylate WC-1, thus modulating its activity .…”
Section: Rapid Biochemical Changes Associated With Conidiationmentioning
confidence: 99%
“…However, the expression pattern of light-regulated genes was the same in the WT and OEblr2-13 strains, indicating that different adaptation mechanisms may be operating. In N. crassa, a negative feedback loop involving the flavoprotein VIVID and phosphorylation by different kinases that destabilize WC-1, and block the transcriptional activity of the WC complex, are the main mechanisms that control adaptation under continuous exposure to light (Schwerdtfeger & Linden, 2003;He & Liu, 2005). T. reesei, a close relative of T. atroviride, has a homologue (ENVOY) of VIVID that might play a similar role in photoadaptation (Schmoll et al, 2005).…”
Section: Enhanced Light Sensitivity In Trichodermamentioning
confidence: 99%
“…A group of early light-induced genes showing transient expression patterns, typical of adaptive responses, have been identified (Lewis et al, 2002). Among these genes, one encodes a second blue-light photoreceptor, VIVID, necessary for adaptation to constant illumination and to detect changes in light intensity (Schwerdtfeger & Linden, 2003). Although other photoreceptors have been found in the N. crassa genome, it has not been possible to assign any function to them.…”
Section: Introductionmentioning
confidence: 99%